Sebaran Ukuran Rajungan (Portunus Pelagicus Linnaeus, 1758) yang Tertangkap Bottom Gillnet dengan Umpan yang Berbeda - Rapi, Nuraeni L; Jumrawati, Jumrawati; Sabir, Muhammad; Wulandari, Sri (Jurnal Riset Diwa Bahari (JRDB), 2023)
Gill net fishing gear is a passive fishing gear that usually blocks the swimming direction of fish, with the addition of bait as a lure is expected to increase the chances of fish that will be used as a target catch willing to enter the fishing gear. aims to analyze the composition of crab catches on different baits and analyze the size distribution of crabs. The expected benefits of this research are as one of the information materials for efficient crab fishermen about the use of chicken intestine waste bait and fly fish against crab catches with bottom gill net fishing gear related to the availability of fish bait stocks that are uncertain and quite expensive prices. This research was conducted in January - February 2022. From the results of the t-test analysis, the tcount value was obtained at 5.014 while the t-table was obtained at 2.042 with a significance value of 0.000. Because the t-count value is greater than the t-table and the significance value is smaller than the real level of 5% or 0.05, it is concluded that there is a difference in catches between the chicken intestine bait group and fly fish bait with an average catch using chicken intestine bait higher than using fly fish bait